Effects of Lifestyles of People with Visual Impairments on Cardiometabolic Risk Markers. (September 2019) - Gawlik, Krystyna; Zwierzchowska, Anna; Rosołek, Barbara
Introduction: The aim of this study was to identify selected cardiometabolic risk markers and determine their correlation with lifestyles of adults with visual impairments. Methods: The study randomly selected 49 people with visual impairments (25 women and 24 men) aged 17–84 years (mean age 58.5 years). Body build, composition metrics, biochemical parameters, level of physical activity, and eating habits were evaluated. Results: Excessive body mass was found in 65% of respondents (72% women and 58% men). Above-typical blood total cholesterol levels were found in 52% of women and 42% of men, low-density lipoprotein (LDL) cholesterol levels in 33% of men and 20% of women, triglyceride levels in 16% of women and 17% of men and glucose in 56% of women and 42% of men. Reduced levels of high-density lipoprotein cholesterol were found in 25% of men and 20% of women. Results showed that 43% of respondents were not involved in physical activity at the recommended level. The use of nicotine was declared by 18% of respondents. No significant correlations were observed for the relationships between physical activity and somatic and biochemical parameters. Eating habits had a significant effect on the prevalence of above-typical LDL cholesterol levels, whereas smoking led to significant differences between study participants due to body mass index and fat percentage. Discussion: Lifestyles of individuals with visual impairments were not entirely healthy. Due to the characteristics of the disability, people with visual impairments are challenged with barriers to living healthy lifestyles. Implications for practitioners: The information obtained here can be used to implement adequate measures to provide equal opportunities for people who are blind or have low vision to lead healthy lifestyles and improve their quality of life.